Uma nova técnica de lavagem de isoladores da rede elétrica de distribuição - Sousa, Rafael Oliveira de (2010)
The work presents a new technique of cleaning of insulators of the grid of distribution of electrical energy. The current process used by all energy company to cleaning of glass and porcelain insulators use a lot of treated water. The new technique proposes the substitution of the cleaning with water for a cleaning with compressed air. This research was strictly experimental, with great laboratory support and field tests for validation. At first the tests of this new methodology of cleaning were done in laboratory. A technique of artificial pollution of insulators was developed for the testes in laboratory. In this stage were used industrial compressors and a system of nitrogen gas in high pressure. In a second moment, still in laboratory, were done several tests with a compressor of high outflow. After this stage of laboratory field tests were done. These tests were done initially in a training center for electricians that simulate the electrical grid. After that the tests were done in lines of distribution of the electrical company, COELCE, with de-energized grid. During all tests the cleaning with compressed air the measurement of the leakage current of insulators was the parameter for the validation of the process. All the tests have done show a environmentally friendly solution, that contributes to the preservation of the environment and effective in the cleaning process.